(untitled) (Journal of Educational Sciences, 2021)
This article conspires the fundamentally important changes that are taking place in almost all spheres of society. Similar changes make it difficult for the development of the younger generation to social adaptation and professional development.Modern Kazakhstan needs competitive people, with highly developed intellectual and communication skills, with organizational skills, capable to achieve their goals.These circumstances determine the increased interest in the study of leadership competencies of future teachers.The scientific work explores the psychological and pedagogical conditions for the forma- tion and development of leadership competences of future teachers.This article is revealing the essence of the concepts of the phenomenon «condition», «psychological and pedagogical conditions», that are providing a purposeful learning process for students in the formation of leadership competencies, which allow go to a qualitatively new level of education in higher education. The elements of the content of innovative forms and methods of teaching are analyzed, the use of which will make the process of form- ing leadership competencies purposeful and more effective. One of the stages of this research was the conduct of primary psychological and pedagogical diagnostics using the method of oral questioning (in- terview), pedagogical training to obtain information about the presence and level of development of the respondents’ leadership competencies and for further analysis of the psychological and pedagogical con- ditions of perfection-oriented leadership competencies of students in a higher school environment. 84 students from M. Auezov South Kazakhstan University and Silkway International University (Shymkent, Kazakhstan) took part in the experiment. Key words: pedagogical conditions, psychological and pedagogical conditions, pedagogical pro- cess, leader, competencies.